PERAN LEMBAGA SWADAYA MASYARAKAT (LSM) KOALISI PEREMPUAN INDONESIA (KPI) KOTA SEMARANG DALAM PEMBERDAYAAN POLITIK PEREMPUAN DI KOTA SEMARANG - sitorus, Candra; ., Purwoko; Astuti, Puji (Journal of Politic and Government Studies, 2015)
The position of women who have tended to become the object of national development is unfair for women. Their space is limited in the domestic region, they are not given space to contribute and participate in public areas, moreover contribute and participate in the region to organize or even practical politics tend to be ignored or even marginalized. Indeed in statute of Indonesia 1945 was never discriminate between men and women, because there are values of justice and equality for men and women, even Political and Electoral Law clearly accommodate women could contribute and participate. The women will be participate not only in domestic areas but they are given space to be able to contribute and participate in public areas in this role and participate in the world of organization and practical politics. Because the law requires that 30% of the management of political party and candidate representatives in the legislature are women as well as in government. This study aims to determine: 1) To know the programs of KPI in Semarang city to support women's empowerment. 2) To determine factors of supporting and inhibiting the implementation of women's empowerment program implemented by KPI in Semarang. In this research use descriptive qualitative study. The aim using qualitative-descriptive methods to describe the role of NGO Koalisi Perempuan Indonesia (KPI) of Semarang in supporting the realization of public disclosure in the form of words or discourse through a proper and systematic interpretation. The results showed: 1) The role of KPI Semarang in empowering women through NGOs carried out through training and mentoring for joining develop independence. In here, the role of KPI Semarang are gathering to learn and motivator for women to know how to organize and politics. 2) Supporting factors in women's empowerment program KPI of Semarang: Cooperation between NGOs and public officials, as well as the support of stakeholders such as governments, NGOs and other private organizations. Inhabiting factors: a) Inhibiting factors are derived from the group is: the lack of awareness and willingness to apply knowledge of the organization and get to know the world of politics. Inhibiting factors from the external: The patriarchal culture is still high in Indonesia resulted in a lot of women are afraid of joining an activist and fight for their rights, they still tend to rely on the ability of men. Keywords: NGOs, KPI, Patriarchy, Women's Empowerment